Inventory and evaluation of Nairobi Animal Orphanage - Hedman, Ellen (2009)
The present BSc thesis is part of a newly established collaboration between the Swedish zoo Skansen and Kenya Wildlife Service (KWS), and constitutes of an inventory of the Nairobi Animal Orphanage (AO). As a refuge for wild animals found orphaned, abandoned or injured throughout Kenya, the AO has grown over the years and reached an unsustainable point where external help is needed for solutions and improvements. The aim of the inventory is to specifically consider the husbandry and enclosures of spotted hyena (Crocuta crocuta), serval (Felis serval), Sykes‟ monkey (Cercopithecus albogularis) and vervet monkey (Chlorocebus aethiops) and with the aid of facts about the species, estimate how well their biological needs are satisfied. Different educational elements are also reviewed since one of the main purposes of the AO is for education. The practical part of the thesis was carried out during three weeks at the AO outside Nairobi, Kenya. Enclosures were measured, photographed, sketched and documented. In addition staff was interviewed and husbandry routines as well as visitor behaviour was observed for evaluation. The results here reveal that in general for the selected species, enclosures a long with some of the husbandry routines are in need of extensive changes to improve animal welfare. There is an overall lack of environmental and behavioural enrichments as well as sufficient space for the animals. The educational parts at the AO are unorganized and inconsistent but have an immense potential considering the sheer number of visitors it can affect. Possible solutions and improvements of enclosures, husbandry and education practises are discussed. The urgent needs for enrichments and in some cases alternative social constellations are proposed. Furthermore, some approaches and developments to enhance the education capacity at the AO are suggested. The economical limitations for this facility are a serious issue, which is why Skansen can become an important resource as well as a guide to improve and promote good animal husbandry and welfare.